Sugarcane Bagasse Ash as a Reinforcing Filler in Thermoplastic Elastomers: Structural and Mechanical Characterizations - Ozorio, Maiza da Silva [UNESP]; Prado dos Reis, Elton Aparecido [UNESP]; Teixeira, Silvio Rainho [UNESP]; Bellucci, Felipe Silva [UNESP]; Job, Aldo Eloizo [UNESP] (Wiley-Blackwell, 2015)
The incorporation of residues as reinforcing fillers in polymer composites has emerged as a viable solution, enabling improvements in the mechanical properties of these materials, and has also resulted in a reduction in the cost of the final product. In this work, sugarcane bagasse ash (SBA) was used as a reinforcing filler in comparison with commercial silica (CS) in thermoplastic elastomers prepared from the compatibility of low-density polyethylene (LDPE) with natural rubber (NR). The composites were obtained by a physical mixture of LDPE and NR with different proportions of CS and SBA using a Haake rotational rheometer. The samples were analyzed by Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and tensile testing. The results show that SBA has similar properties to CS, thus making its use feasible as a reinforcing filler in thermoplastic elastomers. (C) 2014 Wiley Periodicals, Inc.
Keywords: composites; properties and characterization; rubber; synthesis and processing; thermoplastics